Characterisation of the molecular interactions between primary bile acids and fractionated lupin cotyledons (Lupinus angustifolius L.). (1st September 2020) - Naumann, Susanne; Schweiggert-Weisz, Ute; Eisner, Peter
Highlights: Lupin cotyledon significantly adsorbed primary bile acids. A hydrophobic interaction between bile acids and lupin cotyledons was indicated. Bile acid adsorption was independent of lupin protein and dietary fibre. Lupin cotyledon alcohol extracts were rich in flavonoids. Alcohol extracts showed strong molecular interaction with bile acids. Abstract: Interactions between bile acids and plant-based materials, and the related feedback mechanisms in enterohepatic circulation, have been considered targets for lowering cholesterol. This study aimed to identify lupin compounds that interact with primary bile acids on molecular level. Lupin cotyledons were fractionated and bile acid adsorbing activities were investigated using in vitro digestion, equilibrium dialysis and kinetic analyses. Protein- and fibre-enriched fractions significantly (p ≤ 0.05) adsorbed chenodesoxycholic acids (up to 2.33 µmol/100 g DM). Alcohol purification showed that bile acid adsorption is independent of protein and fibre structures. Moreover, high adsorption was observed with an alcohol extract (6.97 µmol chenodesoxycholic acids/100 g DM) that was rich in phytochemicals, such as flavonoids (1842 mg/100 g DM). These results suggest the formation of hydrophobic interactions between polyphenols and bile acids. Further studies of molecular mechanisms are required to define the contributions of polyphenols to the cholesterol-lowering actions of lupins.